Future trend of terminal energy conservation in steelmaking plant: Integration of molten slag heat recovery-combustible gas preparation from waste plastics and CO2 emission reduction. (15th January 2022) - Zhang, Huining; Dong, Jianping; Wei, Chao; Cao, Caifang; Zhang, Zuotai
Abstract: Integration consideration of end-point reproductions like molten slag waste heat high-efficiently recovery and resourceful disposal has a significant influence on establishing more economical and environmental wastes circular network system, due to 0.75billiontonne metallurgical slag with nearly 1500 °C is produced annually, corresponding to 40milliontonne coal theoretically calculated by 100% heat recovery. In this review, the technologies' limitations and their priorities of prevailing heat recovery processes including physical or chemical methods through evaluating the key parameters such as heat recovery rate and granulation performance were discussed. Physical methods like centrifugal granulation have a recovery rate of less than 65% except for better slag particle diameter, and the heat only in the high-temperature range can be recovered efficiently. By contrast, chemical methods have a better heat recovery rate through combustible gas preparation based on slag catalysis, but slag granulation performance cannot be guaranteed. Thus, the collaboration of physical and chemical methods like slag granulation-coal gasification system was proposed, which had an ingenious integration of energy cascade recovery at a wider temperature range, combustible gas preparation like hydrogen and slag granulation. However, this process will consume a great quantity of fossil fuel and emerge some other dangers to the environment, therefore, a cleaner routine of molten slag-waste plastics system was proposed for triple targets above on the premise of carbon dioxide storage and sequestration, which will provide a smart strategy for terminal energy conservation and establishing more economical and environmental wastes circular network system in steelmaking plant. Highlights: A slag heat recovery-gas preparation and CO2 reduction system was proposed. The limitations and priorities of slag heat recovery processes were discussed. The future trend of slag waste heat recovery technology was analyzed. Smart strategy of terminal energy-saving system was provided in steelmaking plant.